Carotid Intimal Thickness and Plaque Predict Prevalence and Severity of Coronary Atherosclerosis: A Pilot Study. (January 2015) - Jeevarethinam, Anand; Venuraju, Shreenidhi; Weymouth, Michelle; Atwal, Satvir; Lahiri, Avijit
We determined whether increased carotid intima–media thickness (cIMT) and prevalence of carotid plaque (CP) are predictive of prevalence and severity of coronary atherosclerosis. Consecutive patients (n = 150) with no history of coronary artery disease (CAD), who underwent both carotid ultrasound and computed tomographic coronary angiography, were included in the analysis. The mean cIMT was higher in patients with CAD than in those without CAD (0.76 vs 0.66 mm, P < .003). In a logistic regression analysis, diabetes ( P = .03) and CP ( P = .02) were associated with significant coronary plaque. Backward selection analysis (after removing nonsignificant variables) showed higher mean cIMT measurement correlated well with prevalence of any coronary plaque ( P = .03) and obstructive coronary plaque disease ( P = .05), whereas presence of CP was a good predictor of both obstructive (>50% stenosis P = .003) and any coronary plaque ( P = .003). In conclusion, CP and cIMT can be useful predictors of prevalence of CAD and its severity.